Mixed convection stagnation point flow of williamson hybrid nanofluid over a non-linear shrinking sheet - Masyfu'ah, Mokhtar; Abdul Rahman, Mohd Kasim; Iskandar, Waini; Nur Syahidah, Nordin (IPMEDIA SDN BHD, 2025)
Hybrid nanofluids have emerged as advanced heat transfer materials for industrial applications. In this study, Alumina (Al₂O₃) and Copper (Cu) nanoparticles, dispersed in a Carboxymethyl Cellulose (CMC)-water-based fluid, are considered to form a non-Newtonian hybrid nanofluid with shear thinning behaviour, chosen for their superior thermophysical properties, stability, and practical applicability in advanced thermal management systems. By incorporating the non-Newtonian behavior of the Williamson fluid model together with the synergistic effects of hybrid nanoparticles, this study achieves a more accurate representation of practical fluid flows in industrial and engineering applications. Through appropriate transformations, the governing equations are reduced to similarity equations, which are then resolved using MATLAB’s bvp4c solver. Model accuracy is verified by comparing the results with an existing model, demonstrating good agreement. This study explores the effects of several fluid parameters, including mixed convection, suction, nanoparticle concentration, and the Williamson parameter, on fluid flow. The results reveal that increased mixed convection and suction enhance heat transfer performance, whereas higher Williamson parameter values and nanoparticle concentrations reduce heat transfer. Overall, the findings provide significant insights into the behaviour of hybrid nanofluids in non-Newtonian flows and offer a theoretical foundation for their application in heat transfer enhancement strategies across diverse engineering systems.